The histone acetylation-related gene signature predicts prognosis and immunotherapy response in stomach adenocarcinoma - Dai, Chen; Su, Rishun; Zhao, Zhenzhen; Guo, Yangyang; Hou, Wenbin; He, Yulong; Liu, Guangyao; Yin, Songcheng; Zhang, Changhua (Frontiers in Oncology, 2025)
BackgroundGastric cancer (GC) is a very aggressive, with extreme heterogeneity and rapid growth, most frequently manifested histologically as stomach adenocarcinoma (STAD). Current evidence suggests that histone acetylation is critical for the origin and development of tumors. However, the significance of histone acetylation-related gene signatures for prognosis of STAD patients and mechanisms of histone acetylation in STAD therapy remains unclear.MethodsWe identified histone acetylation-related genes in STAD from TCGA and constructed eight-gene signatures by utilizing a univariate Cox regression model with the Least Absolute Shrinkage and Selection Operator (LASSO). In addition, a nomogram was plotted to predict the prognostic significance of the established risk model. We examined associations between our gene signature and somatic mutation, immune subtype, clinicopathological features, tumor microenvironment, immune cell infiltration and immune activity, immunotherapy prediction and drug sensitivity. Cell-based assays were performed to determine the relationship between Doublecortin Like Kinase 1 (DCLK1) and the proliferation, migration and oxaliplatin resistance of GC cells in vitro. Immunohistochemical experiments were used to explore the relationship between DCLK1 and clinicopathological parameters.ResultsA prognostic model composed of eight histone acetylation-related genes in STAD was developed. Based on median risk score, the STAD patients were equally assigned into two groups of high- and low-risk, where high-risk represented a less favorable prognosis than low-risk. The two groups showed significant differences with respect to somatic mutation, immune subtype, clinicopathological features, tumor microenvironment, immune cell infiltration and immune activity, immunotherapy prediction and drug sensitivity. The results generated during Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses suggested that Differentially Expressed Genes (DEGs) in the two groups were involved in cancer-related processes and pathways. Cell-based assays indicated that DCLK1 is a promoting factor in gastric cancer and can promote oxaliplatin resistance in gastric cancer cells. Increased DCLK1 expression was also associated with Borrmann’s Type, depth of invasion, lymph node metastasis, and TNM stage in GC patients.ConclusionA novel histone acetylation-related gene signature, which possesses potential value in predicting the prognosis and immunotherapy effectiveness regarding STAD patients, was developed. This signature may serve as a reliable biomarker for prognosis of STAD and promote the identification of novel treatment targets for STAD. Furthermore, DCLK1 exhibited oncogenic roles and may be a new target for STAD therapy.